(untitled) - Martin Gijon, Mario (Romanica Olomucensia, 2013)
This paper analyses the translations from Rainer Maria Rilke by Juan Andres Garcia Roman, from Robert Creeley by Marcos Canteli and from Philippe Jaccottet by Rafael-Jose Diaz. It intends to analyse the reasons and consequences of a poet's dedication to translation. In these three cases, the paper observes the different ways of translation by these poets and the relation of their translations to their own literary works. This intensive dedication to the translation of three great poets of German, English and French literatures shows the breadth of interests of the most innovating authors in contemporary Spanish poetry.
Keywords: Spanish poetry; XXth-XXIth centuries; translation; comparative literature.